Model Kebijakan Permukiman Kampung Code Utara di Tepi Sungai Code - Putri Ayodiya, Natalia Riza (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2014)
River control area which actually protected area has been converted into a densely populated residential area. This case happened in the riverside of code, particulary in Kampung Code Utara which is located in the city of Yogyakarta. Besides a part of protected area, it also part of disaster-prone area of Merapi Mountain. Appropriate housing policies need to overcome it. The exact settlement policies need to consider the wishes of the people because basically people have the right to choose a place to stay so the policy can be implemented effectively and efficient. Therefore this study aims to formulate policy model of Kampung Code Utara. This study use a qualitative approach. Data collection techniques used were interview and documentary techniques. Further, data analysis techniques use qualitative descriptive analysis techniques. The population of this study were as many as 193 people. The sample of this study were as many as 20 people from the community of Kampung Code Utara using purposive sampling techniques. The result of this studies show people in Kampung Code Utara decide to stay at riverside of Code because of Kampung Code Utara accessibility which is nearby service center and supported by diverse and affordable transportation. Relocation could be applicable in urban or rural area which the lan is available from Kraton Yogyakarta and the cost to build a flat is payed by Ministry of Public Housing or privat side.